The Strategy Of Islamic Counseling Guidance In Efforts To Form The Charakter Of Students At PPTQ Muhammadiyah Atmo Wahjono Sukoharjo - Khotijah, Siti; Sarjono, Joko; Mukhlisah, Iffah (UMSU, 2024)
The aim of this research is to describe the BKI ustaz's strategy in forming the character of the santri, to find out the dominant character possessed by the santri and the supporting and inhibiting factors in the formation of Islamic character at the Tahfizhul Qur'an Muhammadiyah Atmo Wahjono Islamic Boarding School. Using a qualitative descriptive approach, data was collected through in-depth interviews, observation and documentation involving ustaz, students and Islamic boarding school caregivers. The results of the research show that the character building of santri is carried out in several forms, namely: approaching the ustadz and santri, getting used to the santri's lifestyle, inauguration of IPM, and regular counseling services for santri who need it. The dominant santri characters are: the character of gratitude, the character of faith, and the character of being kind to parents. The supporting factors are: good management performance, good interaction between students and ustadz, guardians of students who support the implementation of the regulations, the presence of Islamic boarding school ustadz (BKI) and psychiatrists and support from community leaders. Inhibiting factors are: student behavior patterns which are sometimes difficult to regulate and lack of support from student guardians in educating students, especially students who are experiencing problems.